Amphioxus (Branchiostoma floridae) superTranscriptome - Holland, P; Herrera-Ubeda, C; Li, G (University of Oxford, 2020)
Amphioxus (Branchiostoma floridae) cDNA superTranscriptome assembly BfsuperV5 was downloaded from the IncDNA-BF (Integrative cDNA library for Branchiostoma floridae) database (http://139.129.29.118/IncDNA) made available by Prof. Zhiliang Ji and Dr. Yangmei Qin of the School of Life Sciences, Xiamen University, Xiamen, China (appo@xmu.edu.cn). Hox genes were then assembled manually to remove and correct an artefactual fusion between 6 distinct Hox genes and a lncRNA (giving 215,495 sequences). The version deposited here includes this adjustment. Use of these data should acknowledge the IncDNA-BF (Integrative cDNA library for Branchiostoma floridae) database (http://139.129.29.118/IncDNA) and the publication cited in this ORA-Data entry. Files included: BfsuperV5_fix.fa = fasta file of all sequences BfsuperV5-4_FIX.gtf = tab-delineated text file in gtf format giving feature coordinates and putative identities of transcripts within superTranscripts. Tabs are: (1) seqname [equivalent to contig ID or gene name in Supplementary Data]; (2) source [superTrancript]; (3) feature [transcript, exon or CDS (coding sequence)]; (4) start of feature; (5) end of feature; (6) score [dot]; (7) strand [+]; (8) frame [dot]; (9) attribute [gene_id; transcript_id; gene_Name = example blast hit, uniprot code; Note = putative gene name from uniprot blast hit blast only]